2A-linked bi-, tri-, and quad-cistrons for the stepwise biosynthesis of β-carotene, zeaxanthin, and ketocarotenoids in rice endosperm - Jeong, Ye Sol; Ku, Hyung-Keun; Jung, Young-Joo; Kim, Jae Kwang; Lee, Kyoung Bok; Kim, Ju-Kon; Lim, Sun-Hyung; Lee, Dongho; Ha, Sun-Hwa (Metabolic engineering communications, 2021)
Foot-and-mouth disease virus (FMDV) 2A constructs have been successfully used for the production of “Golden Rice”, a β-carotene producing rice strain. However, to allay public fears and opposition to plants carrying a mammalian pathogenic viral sequence, 2A-like synthetic sequences from Thosea asigna virus and Infectious myonecrosis virus were used to coordinate the coexpression of carotenoid biosynthetic genes. Here, up to four carotenogenic genes encoding PSY, CRTI, BCH and BKT were concatenated and produced β-carotene, zeaxanthin, and ketocarotenoids (astaxanthin and adonixanthin) in transgenic rice seeds displaying color variation due to the difference in carotenoid content and composition. •Carotenogenic genes upto four were concatenated via three 2A-like peptides into single cistrons.•Polycistrons stepwisely biosynthesized β-carotene, zeaxanthin and ketocarotenoids in rice.•A Thosea asigna viral 2A peptide is a good alternative to FMDV 2A for plant biotechnology.